EVALUATION OF EFFECTIVE WEED MANAGEMENT STRATEGY FOR BT COTTON - HARGILAS,; G. S. AMETA,; SUBHASH CHANDRA JAT,; D. P. SAINI, (The Bioscan, 2015)
A field experiment was conducted at Agricultural Research Station, Banswara (Raj.) during rainy season of 2014 to evaluate effective weed management strategy for Bt cotton. The experiment consisted of 9 treatments of PE (Pendimethalin) and POE (Quizalofop ethyl, pyrithiobac sodium and glyphosate) herbicides with weed free and weedy checks was laid out in randomized block design with three replications. Results revealed that the sequential use of pendimethalin 30 EC @1.0kg a.i ha-1 (PE) followed by pyrithiobacsodium 10 EC @ 62.5g a.i ha-1 + Quizalofop ethyl 5 EC @ 50g a.i ha-1(POE) at 25 DAS with one hoeing at 45 DAS has resulted in the lowest weed density of 19.67 and 12.33 with lowest weed dry weight of 15.73 and 10.13 g m-2 recorded at 30 and 60 DAS, respectively with the lowest total weed dry matter of 258.56kg ha-1, which ultimately increased seed cotton yield significantly (4389kg ha-1) with maximum B: C ratio of 4.74 against 3.98 calculated in weed free plot. The highest weed control efficiency of 96.08% was calculated under this treatment.